Influence of psycho-demographic factors on fear of crime among multi-nationals in Lagos, Nigeria. (2011)
The influence of personality variables, perceived security, perceived police effectiveness and demographic factors as they relate to fear of crime (FOC) in convenience samples of multi-nationals (N=202) and Nigerian nationals living in Lagos, Nigeria, was investigated. Nigerians reported the highest level of FOC while Americans reported the lowest level of FOC. Results indicate the combined influence of psychological factors and an independent effect of perceived security. Demographic factors jointly predicted FOC and gender. Perceived police effectiveness and perceptions of security were positively correlated. Significant differences related to FOC were found among all national groups. These findings suggest that individuals and government at all levels should be aware that FOC varies among foreigners and that FOC is predicted by perceived security and gender. Psychological and social relief efforts to meet specific socio-cultural and demographic differences in the country may contribute to a reduction in FOC in Nigeria.